2015
DOI: 10.1016/j.nefro.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos celulares y moleculares de la nefropatía diabética, rol del VEGF-A

Abstract: The prevalence of diabetes mellitus increased during the last century and it is estimated that 45% of the patients are not diagnosed. In South America the prevalence of diabetes and chronic kidney disease (CKD) increased, with a great disparity among the countries with respect to access to dialysis. In Ecuador it is one of the main causes of mortality, principally in the provinces located on the coast of the Pacific Ocean. The greatest single cause of beginning dialysis is diabetic nephropathy (DN). Even using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
1
9
0
4
Order By: Relevance
“…The up- and downregulation of the podocyte VEGFA levels during renal development led to glomerular disease. [34] This study identified that VEGFA was a key gene that was downregulated in DN, consistent with previous studies. Sivaskandarajah et al [35] found that selective knockout of VEGFA in glomerular podocytes of diabetic mice resulted in a significant increase in proteinuria with severe glomerular scar formation and increased apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…The up- and downregulation of the podocyte VEGFA levels during renal development led to glomerular disease. [34] This study identified that VEGFA was a key gene that was downregulated in DN, consistent with previous studies. Sivaskandarajah et al [35] found that selective knockout of VEGFA in glomerular podocytes of diabetic mice resulted in a significant increase in proteinuria with severe glomerular scar formation and increased apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Chemerin participates in inflammation, obesity, and insulin resistance by regulating glucolipid metabolism and promoting adipocyte differentiation [ 12 ]. Vascular endothelial growth factor (VEGF) can stimulate vascular endothelial cell division and enhance vascular endothelial cell permeability, thus promoting vascular endothelial cell proliferation, differentiation, and angiogenesis [ 13 , 14 ]. However, the correlation of Chemerin and VEGF with DN has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Quienes la padecen presentan un alto riesgo de desarrollar nefropatía diabética y entre el 20 y el 50 % de ellos tiene riesgo de sufrir insuficiencia renal crónica terminal (IRCT) y necesitar de diálisis o trasplante de riñones [1][2][3] . Se sabe que cerca del 40 % de los casos nuevos de IRCT se debe a esta patología.…”
unclassified
“…En consecuencia, se estima que la prevalencia mundial de DM tipo 2 aumentará, de los 171 millones que había en el año 2000, a una cifra de, al menos, 366 millones para el año 2030. Por tanto, un mayor número de personas llegará a padecer IRCT y requerir terapia renal sustitutiva 6,8 . Las así llamadas "complicaciones microvasculares" (retinopatía y nefropatía) son responsables directas de la morbilidad más frecuentemente asociada a la DM.…”
unclassified
See 1 more Smart Citation